An annotated and illustrated checklist of the Indian cuckoo wasps (Hymenoptera: Chrysididae) - Rosa, Paolo; Aswathi, Pokkattu Gopi; Bijoy, Chenthamarakshan (Zootaxa, 2021)
An illustrated and updated checklist of the Indian Chrysididae is presented, including synonyms and distributional summaries. The list includes 105 species in 20 genera. Six species are described as new: Elampus gladiator Rosa, sp. nov. (Himachal Pradesh, Jammu & Kashmir, and Uttar Pradesh), Chrysis aswathiae Rosa, sp. nov. (Tamil Nadu, elegans species group), Chrysis baldocki Rosa, sp. nov. (Tamil Nadu, smaragdula group), Chrysis bernasconii Rosa, sp. nov. (Tamil Nadu, subsinuata group), Chrysis polita Rosa, sp. nov. (West Bengal, Uttaranchal, Myanmar, ignita group), and Chrysis travancoriana Rosa, sp. nov. (Kerala and Tamil Nadu, praecipua group). Six species are newly recorded: Chrysis hecate Mocsáry, 1889; Chrysis jalala Nurse, 1902; Chrysis obscura Smith, 1860; Istiochrysis ziliolii Rosa & Xu, 2016; Praestochrysis furcifera (Bingham, 1903); Primeuchroeus siamensis (Bischoff, 1910). Two new synonymies are proposed: Chrysis abuensis Nurse, 1902, syn. nov. of Chrysis wroughtoni du Buysson, 1896b; Chrysis nursei Bingham, 1903 syn. nov. of Chrysis gujaratica Nurse, 1903a. Holopyga (Hedychridium) virescens Mocsáry, 1914 is transferred to the genus Hedychridium Abeille de Perrin, 1878; the name Hedychridium virescens (Mocsáry, 1914) results a secondary homonym of Hedychridium virescens du Buysson, 1908 and it is here replaced with the new name Hedychridium mocsaryi Rosa, nom. nov. Chrysis cotesi du Buysson, 1893, sp. resurr. is here revalidated from the previous synonymy with Chrysis palliditarsis Spinola, 1838. Chrysis bahadur Nurse, 1903a is transferred from the ignita group to the splendidula group, Chrysis bhavanae Bingham, 1903 is transferred from the ignita group to the maculicornis group, and Chrysis thakur is transferred from the smaragdula group to the oculata group. Chrysis nila Bingham, 1903 and Chrysis variipes Mocsáry, 1911 are included in the newly established nila group. Spinolia kashmirae Kimsey in Kimsey & Bohart, 1991 is classified as unnecessary replacement name. The name Parnopes oberthuri du Buysson, 1904 is here emendated into Parnopes oberthueri (currently Cephaloparnops oberthueri). Potential erroneous data, misidentifications and dubious distributional records that may exist in the literature are also identified. We examined almost all type specimens, excluding taxa described by Cameron and Smith. We provide a key to Indian genera, including those expected for the country and not yet recorded, and colour images of type and non-type specimens belonging to 82 species.